Effect of Leaflet-Based Health Education on Spiritual Well-Being and Quality of Life Among Patients Living with HIV/AIDS at Immanuel Hospital, Bandung - Saur Mian Sinaga (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Human Immunodeficiency Virus (HIV) is a chronic sexually transmitted infection that progressively weakens the immune system. If untreated, HIV can develop into Acquired Immunodeficiency Syndrome (AIDS), a condition characterized by severe immune suppression and increased vulnerability to life-threatening infections. Beyond physical complications, people living with HIV/AIDS often experience unmet spiritual needs that negatively affect their overall quality of life. Health education interventions using simple and accessible media, such as leaflets, may support spiritual well-being and improve quality of life. Objective: This study aimed to examine the effect of leaflet-based health education on spiritual needs fulfillment and quality of life among patients with HIV/AIDS at Immanuel Hospital, Bandung. Methods: A quasi-experimental study design with a pretest–posttest approach was conducted in August 2022. A total of 63 patients with HIV/AIDS were recruited using purposive sampling. The intervention consisted of structured health education delivered through leaflets focusing on spiritual support and coping strategies. Data were collected through validated questionnaires measuring spiritual needs and quality of life before and after the intervention. Statistical analysis was performed to assess changes following the educational intervention. Results: The findings demonstrated a significant improvement in spiritual needs fulfillment and overall quality of life after the leaflet-based health education intervention. Participants showed increased spiritual well-being and better perceived quality of life following the intervention. Conclusion: Leaflet-based health education is an effective intervention to enhance spiritual needs fulfillment and improve quality of life among patients with HIV/AIDS. Incorporating spiritual-focused educational materials into routine nursing care may contribute to holistic patient management.